Muslim women’s activism: A comparative study of the educated female perceptions in Malaysia and Pakistan / Aurangzaib Alamgir - Aurangzaib, Alamgir (2015)
The status of Muslim women in society is one of the most contested subjects in the academic scholarship for the last couple of decades. This debate on the position and status of Muslim women can be traced to the 1980s Islamic revivalist movements throughout the Muslim world. These revivalist movements gave rise to political Islam and posed severe challenges to women‟s rights organizations involved in promoting democracy and respect for human rights, particularly Muslim women‟s rights. Since then, Muslim women groups have increased considerably in number and are at the forefront in countering the use of religion by Islamic activists to justify women‟s oppression. Sisters-in-Islam Malaysia (SIS) and Women‟s Action Forum Pakistan champion women‟s rights in their respective countries based on an Islamic framework and believe that it is not Islam that discriminates against women but the male-dominated interpretation of the Qur‟an and patriarchal social structures. They also believe that sometimes cultural practices that are justified in the name of Islam makes Muslim women inferior to men. An important approach that SIS and WAF employ in promoting women‟s rights is to reinterpret and reread the Qur‟an historically and culturally. They attempt to reinterpret and understand Islam as one that is more affirmative of women‟s rights and status and focus at the essence of Islam as a religion that emphasizes equality, egalitarian and justice between genders The study focuses on the perception of Muslim female educated elites about SIS, WAF and their strategies and programs. The study employs quantitative survey complimented by qualitative interviews. The respondents for the quantitative survey are final year female Muslim students from the University of Malaya, Malaysia (UM) and University of Karachi, Pakistan (KU). The reason why students are chosen as respondents for the study is that they are the future leaders and after completing their education, they may occupy positions in government and private machinery and later on some may hold positions at the policy level. Stratified random sampling is used to identify the sample size for the quantitative survey. For in-depth analysis of the issues, qualitative interviews are conducted with 10 respondents and they come from various backgrounds such as academicians, Shar’iah lawyers and women‟s rights activists. The quantitative data is analyzed through SPSS for statistical findings while the qualitative data is analyzed to gain an in-depth understanding of the reasons for the support or the nonsupport of SIS‟s and WAF‟s strategy and programs. The study finds that in some areas SIS and WAF are received well by the respondents of the study and in others they are criticized. In terms of field of study, Science students are more positive about SIS/WAF and their strategies and programmes, the Islamic Studies students are in the middle and Social Science Students are negative in their perception. Although, the interview respondents agree with the issues of advocacy of SIS and WAF yet they make varied conclusions of how these issues should be addressed. There are different factors that shape this perception, for instance, the choice of words SIS and WAF use while doing advocacy on women‟s rights, their eligibility and expertise in interpreting the Qur‟an and making Ijtehad on priority basis. In addition, some believe that if the existing interpretations of the Qur‟an are male-centred, with the involvement of women it would be women-centred. Furthermore, the double standards of the Muslim women in both Malaysia and Pakistan also shape this perception as they literally agree that polygamy is Islamic and favor its practice but practically they do not prefer it for themselves.